365 Cognitive Behavioral Therapy and Light Dark Therapy for Postpartum Insomnia Symptoms: Findings from a Randomized Controlled Trial. (3rd May 2021) - Verma, Sumedha; Quin, Nina; Astbury, Laura; Wellecke, Cornelia; Wiley, Joshua; Davey, Margot; Rajaratnam, Shantha; Bei, Bei
Abstract: Introduction: Symptoms of insomnia are common in the postpartum period and are associated with a range of negative outcomes. Despite this, interventions to improve maternal postpartum sleep remain scarce. Cognitive Behavioral Therapy (CBT) and Light Dark Therapy (LDT) target two different mechanisms to reduce sleep disturbance. This randomized controlled trial examined the efficacy of CBT and LDT against a treatment-as-usual (TAU) condition in reducing maternal postpartum insomnia symptoms. Methods: Nulliparous women 4–12 months postpartum with self-reported symptoms of insomnia (Insomnia Severity Index scores [ISI] >7) were included; excluded were those with: current severe health/psychiatric conditions, unsettled infant behaviors, sleep-affecting medication use and photosensitivity. Eligible women were randomized 1:1:1 to 6 weeks of CBT (CBT for insomnia and fatigue), LDT (morning bright light therapy, evening light hygiene), or TAU. Interventions were therapist-assisted and personalized through two telephone calls and included automated self-help intervention materials (i.e., emails) delivered over six weeks. Symptoms of insomnia (ISI; primary outcome), fatigue, sleepiness, depression, and anxiety were assessed at baseline, mid-intervention, post-intervention, and 1-month post-intervention. Analyses were intention-to-treat latent growth models. Results: 114 women were randomized (mean age = 32.20 ± 4.62 years) and 108 women completed the intervention. Compared to TAU, symptoms of insomnia significantly reduced from baseline to post-intervention in both CBT and LDT groups (p-values <.001), with very large effect sizes (d > 1.5) at post-intervention; gains were maintained at follow-up. Fatigue symptoms significantly reduced in the CBT group (p<.0001; d = 0.85) but not LDT (p = 0.11) compared to TAU at post-intervention; gains were maintained for CBT at follow-up. Group differences in sleepiness, depression, and anxiety were nonsignificant (all p > 0.08). Conclusion: Therapist-assisted self-help CBT and LDT with different therapeutic mechanisms are both efficacious for reducing maternal insomnia symptoms during the postpartum period. Findings were mixed for fatigue, sleepiness and mood. Future research on predictors of treatment responses is needed. Support (if any): Australian National Health and Medical Research Council, Department of Education RTP Scholarship. Lucimed SA supplied light therapy glasses. Funders had no role in design/implementation of the trial. ANZCTR: ACTRN12618000842268.